Flow‐synchronized NIPPV with double‐inspiratory loop cannula: An in vitro study. Issue 2 (19th November 2020) - Moretti, Corrado; Lista, Gianluca; Carnielli, Virgilio; Gizzi, Camilla
Abstract: Background: Although short binasal prongs (SBP) are the most common interface for noninvasive ventilation, the "double‐inspiratory loop cannulas" (DILC) have recently been introduced into many neonatal intensive care units. DILC show advantages over SBP, including reduced nasal trauma and increased comfort. However, their higher intrinsic resistance may compromise ventilation. Our aim was to test a new, low resistance DILC interface. Methods: A test lung was programmed to simulate preterm neonates (500–2000 g BW) with moderate‐to‐severe respiratory distress syndrome. The artificial nose was designed to keep prongs‐to‐nares leaks to around 30%. Giulia® ventilator (GINEVRI srl) was used to provide nasal continuous positive airway pressure (NCPAP) and flow synchronized nasal intermittent positive pressure ventilation (NIPPV). NCPAP was set at 4–10 cmH2 O and synchronized‐NIPPV (SNIPPV) at peak inspiratory pressure, 15–20–25 cmH2 O; inspiratory time, 0.3–0.5 s; and positive end‐expiratory pressure, 5–8 cmH2 O. Four sizes of Sync‐flow Cannula® (GINEVRI srl) were tested. The Sync‐flow Cannula® was compared with Neotech RAM® cannula and Ginevri SBP®. The outcome measures were the flow/pressure relationship through the four Sync‐flow Cannula® sizes, the difference in resistance, the drop in ventilator‐alveoli pressure measured by the test lung and the system response time during flow‐SNIPPV. Results: The smaller DILC sizes had the lowest flow‐pressure ratio. The resistance of the RAM® cannula was significantly higher compared to the other interfaces ( p < .001). With 30% leaks, there was a 4–38% ventilator‐alveoli drop in pressure, depending on interface size. The system response time was excellent ( 65–70 ms). Conclusions: With about 30% leaks, the Sync‐flow Cannula® interfaces result in good pressure transmission and give optimal performance for flow‐SNIPPV. Clinical studies are needed to confirm the clinical relevance of these data.